Gestión del cambio y el teletrabajo (2014)
In the development of the monograph there are demonstrated fundamental topics orientated to the identification of the necessary conditions to achieve the ideal performances in a process of telework; basing this one on a specific model of the management of the change proposed by Jhon Kotter. Across this one it is achieved to identify and to analyze the practices for the definition and establishment of a new form of work. Also they are defined a few actions of conceptual, procedural type, actitudinal and legally that drive to an effective application of the telework to level organizacional, whose final aim is to orientate to all those organizations that they want to implement this model and to have the minimal knowledge that help to the implementation with this one. The flexibilización of the working place, in particular telework represent a very important source of savings in companies and learn how people area actually working is perhaps the biggest challenge of this iniciative. Is basically seeks to address two indicators: activity and productivity. Thanks to the first we will learn how many hours the employee dedicated to his work, It is to say, the dedicated time dedicated to his day, and the second looks for how many hours are devoted to activities considered to be productive for the company. Have information that all the indicators give us, will be possible to establish the program evaluation in each company.